Odpowiedzi

2010-01-24T16:41:10+01:00
A)(15x-10a)-(2x-3)= 15x-10a-2x+3=13x-10a-3
b)4ab-3a+9ab+2a= 13ab-a
c)3x-3y-4y+4= 3x-7y+4
d)5ab-3ab-6a+6a-9=2ab-9
Najlepsza Odpowiedź!
2010-01-24T16:42:18+01:00
A) 5 (3x-2a) - (2x-3) = 15x - 10a - 2x + 3 = 13x - 10a + 3
b) 4 ab- 3 (a+3ab) +2a = 4ab -3a - 9ab + 2a= -5ab -a
c) -3 (-x+y) -2x (2y-2) = 3x-3y -4xy +4x= 7x - 3y -4xy
d) 5ab -3 (ab-2a ) + 3 (2a-3 ) = 5ab -3ab+6a + 6a-9 = 2ab +12a - 9

prosze o naj ;] ;)
2010-01-24T16:46:43+01:00
A) 5(3x-2a) - (2x-3) = 15x-10a - 2x+3 = 13x - 10 + 3
b) 4ab-3(a+3ab)+2a = 4ab-3a-9ab+2a = -5ab-a
c) -3(-x+y)-2x(2y-2) = 3x-3y-2xy+2y = 3x-y-2xy
d) 5ab-3(ab-2a)+3(2a-3) = 5ab-3ab+6a+6a-9 = 2ab+12a-9